2021
DOI: 10.13073/fpj-d-20-00076
|View full text |Cite
|
Sign up to set email alerts
|

Biological Durability of Cross-Laminated Timber— The State of Things

Abstract: Cross laminated timber (CLT) is a mass timber product that is gaining popularity in construction within North America. CLT is made up of wood, a building material of biological origin. Therefore, these materials are at a risk of decay upon intrusion of moisture, a situation that could lead to loss of confidence in the material. Ensuring durability and optimum performance of building elements throughout their expected service life will require an understanding of the potential for decay and the possible consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The benefits of MT-based buildings would be their low carbon emission, short construction time, and cost-effectiveness. However, their durability could be of great concern [10][11][12][13][14]. Figure 1 shows schematics of different types of mass timber.…”
Section: Properties Of Wood and Timbermentioning
confidence: 99%
“…The benefits of MT-based buildings would be their low carbon emission, short construction time, and cost-effectiveness. However, their durability could be of great concern [10][11][12][13][14]. Figure 1 shows schematics of different types of mass timber.…”
Section: Properties Of Wood and Timbermentioning
confidence: 99%
“…CLT panels are a form of engineered wood products (EWP) developed by laminating sawn boards together, commonly by face lamination only (although it can also include edge bonding); the boards are arranged with each layer perpendicular to the previous. Sustained exposure to moisture during construction, in the event of heavy rainfall or plumbing leaks post-construction, can cause moisture gain and lead to possible decay [11][12][13]. A moisture content (MC) exceeding 20% provides an optimum condition for fungal decay in timber products [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Moisture management is one of the most important considerations when working with timber during construction and in service. Moisture management practises and protocols need to target minimising weathering, moisture gradient (MG) development and elevated MC, reducing the chance of dimensional instability, loss of airtightness, biodegradation and mould growth [13,[18][19][20][21]. Previous studies showed that the location of panels, type of elements (wall, roof, floor), and connection type can affect the moisture gain and drying requirements to return the panels to optimum MC levels [6,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, currently most CLT are not treated with preservatives and the strategy for durability is restricted to keeping the wood dry. CLT treatment options are needed to address the inevitable need for supplemental protection (Wang et al 2018, Udele et al 2021.Research is underway on the efficacy of common wood preservatives when applied to CLT panels (Mankowski et al 2018(Mankowski et al , 2020(Mankowski et al , 2022. However, the best way to apply such preservatives requires investigation.…”
mentioning
confidence: 99%
“…However, currently most CLT are not treated with preservatives and the strategy for durability is restricted to keeping the wood dry. CLT treatment options are needed to address the inevitable need for supplemental protection (Wang et al 2018, Udele et al 2021.…”
mentioning
confidence: 99%